A statistical model of irradiation hardening induced by non-periodic irradiation defects. (August 2021) - Cui, Wei; Cui, Yinan; Liu, Wei
Abstract: Numerous efforts have been made to develop the irradiation hardening models, due to their important role in nuclear reactor design and service lifetime prediction. Most of the models are based on the dislocation line tension approximation, by assuming a periodic array of irradiation defects. The random distribution effect is also generally taken into account from a fully deterministic perspective, such as the well-known Bacon-Kocks-Scattergood model. Different from these previous studies, this work is aimed at developing a statistical irradiation hardening model by systematically coarsening the interaction mechanism between dislocation and non-periodic irradiation defects. The cumulative distribution function of the critical shear stress to overcome the irradiation defect barrier is obtained through the analytical derivation, and is lumped into a 2D Monte Carlo model to predict the mechanical response of irradiated material. The prediction results agree very well with three-dimensional discrete dislocation dynamics results and experimental data. Graphical Abstract: Image, graphical abstract